Application of Electrodialysis Process for Reduction of Electrical Conductivity and COD of Water Contaminated By Composting Leachate - Parsa, Nazila; Khajouei, Golnoosh; Masigol, Mohammadali; Hasheminejad, Hasti; Moheb, Ahmad (Civil Engineering Journal, 2018)
The presented paper describes an experimental study to reduce electrical conductivity (EC) of composting leachate-polluted water by using electrodialysis (ED) process. High efficiency, simple operation, low waste generation and selectivity are considered as major advantageous of applying ED process. Along with evaluation of ED method for desalination, the possibility of the process for COD (chemical oxygen demand) removal was also studied. The impact of- applied voltage, feed concentration and process time on ED performances were investigated. Increasing of the applied voltage and decrease of feed concentration enhanced the reduction of EC and improved the COD removal from the sample. At optimal condition (Voltage=10 Volt, feed solution=Cf/4 and time operation=120 min), the reduction of EC and COD removal were 92.7%, and 83.8%, respectively. Applying higher voltage and using more feed solution concentrations resulted in more energy consumption. The obtained results showed that ED method can be considered as an acceptable method to reduce salt and organic content.